Aspectos socioeconômicos de sistemas de uso da terra na Comunidade São Pedro, Projeto Agroextrativistas (PAE) Eixo Forte, Santarém, Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2013)
This study aims to assess socioeconomic and productive aspects of production systems developed by smallholders of São Pedro Community, Eixo Forte Agroextractive Project, Santarém, Pará. It was applied structured interview with to 22 smallholders families. This interview covered economic, environmental, socioeconomic and productive aspects. The research was descriptive, in case study, with non-probabilistic sampling. For data analysis we used descriptive statistics and the results are presented in tables and graphs. It was observed that the farmers had low education, being young with regard to age, income from different agricultural and non-agricultural activities. Cassava was the most cultivated temporary species in production systems, and cashew, mango and acai, among permanent. The creation of chickens had great importance in household consumption, and contributes in generating income on household budgets.
Keywords: sistemas produtivos; agricultura familiar; assentamentos rurais; Amazônia; CNPQ:: CIÊNCIAS EXATAS E DA TERRA